2022
DOI: 10.56897/iefr.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Industry and Digital Financial Inclusion for Economic Development of an Inclusive Society in Indonesia

Abstract: This study aims to analyze cointegration relation between Fintech industry and digital financial inclusion in 34 provinces of Indonesia. Using the Binary Logistic Model, Panel Cointegration Test, and Panel Regression Model methods, this study concludes that there is a long-term relationship between fintech transactions and digital financial inclusion. it means economic development of an inclusice society in 34 provinces in Indonesia can be fufilled through fintech and digital inclusion. To analyze the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…The results of testing the six hypotheses of the present study go in line with the finance-growth hypothesis (Schumpeter, 1912;Fry, 1988;Pagano, 1993), and also provide support for the prior studies that reported a positive relationship between FI and economic growth (such as Musau, Muathe & Mwangi, 2018;Chinoda, Kwenda & McMillan, 2019;Nada, 2019;Oladimeji & Adegbite, 2019;Hu, Liu & Peng, 2020;Huang, Kale, Paramati & Taghizadeh-Hesary, 2020;Sayed, Abbas & Touny, 2020;Patron & Pekhalskii, 2021;Cheumar & Yunita, 2022;Chuc et al, 2022;Ozturk & Ullah, 2022;Younas et al, 2022). Two theoretical contributions are made by the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The results of testing the six hypotheses of the present study go in line with the finance-growth hypothesis (Schumpeter, 1912;Fry, 1988;Pagano, 1993), and also provide support for the prior studies that reported a positive relationship between FI and economic growth (such as Musau, Muathe & Mwangi, 2018;Chinoda, Kwenda & McMillan, 2019;Nada, 2019;Oladimeji & Adegbite, 2019;Hu, Liu & Peng, 2020;Huang, Kale, Paramati & Taghizadeh-Hesary, 2020;Sayed, Abbas & Touny, 2020;Patron & Pekhalskii, 2021;Cheumar & Yunita, 2022;Chuc et al, 2022;Ozturk & Ullah, 2022;Younas et al, 2022). Two theoretical contributions are made by the present study.…”
Section: Discussionsupporting
confidence: 88%